Investment attractiveness of the Odessa region of Ukraine: key factors and indicators - Iran, K.; Liventsov, R. (Journal of Education, Health and Sport, 2025)
The article is devoted to the analysis of the investment attractiveness of the Odessa region of Ukraine. The main factors of the investment attractiveness of the region are considered, the level of investment activity in dynamics is analyzed. Priority areas of stimulation of investment activity of the Odessa region are determined.